ANALISIS PENGENDALIAN KUALITAS PRODUK BERAS PENGGILINGAN PADI KELILING DENGAN METODE SIX SIGMA - Saptomo, Heri Yulius; Sudarwadi, Dirarini; Irmawati, Fika (Cakrawala Management Business Journal, 2023)
ABSTRACT This study aims to analyze the Quality Control of Mobile Rice Milling Rice Products in Prafi SP2 is under control or not yet controlled and to find the causes of defective product damage in the company with the Six Sigma method. The type of research used is two mixed techniques or mix methods. The subject in this study was the Grandong Saroja rice mill in Desay village, Prafi sub-district, Manokwari district. The object used is the amount of Grandong Saroja's rice production and the number of defects for the period in March 2021-March 2022. The primary data used are observations, interviews. Secondary data obtained from data on the number of production and the number of defective products The results showed that controlling the quality of rice products using the Six Sigma method in the DMAIC concept, it is known that the amount of production in March 2021-March 2022 is 167000Kg with the number of defective products in production of 667Kg, indicating that Grandong Saroja is still at the control limit at the five six sigma level, namely 4, 15 defects out of a million opportunities from the six sigma level, i.e. 3,4 defects are equal to probability.